Moral Literacy in Historical Stories of National Heroes: Studies in Character Educations on History Learning at Surakarta High School - Samsi Haryanto, Yudi Hartono, Asrowi, Mulyoto dan (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
A history usually presents a hero in the chronology of its story. Hero stories containimportant values as a material of moral literacy for students. The potential heroes storiesfor character education. Character education is a value education process which based onthe philosophy of humanistic education. In that context, the relevant learning model is aconstructivist model such as Discovery Learning, Problem-Based Learning, and Project-Based Learning. By these models and based on Lickonas view about morality as thereference of character education. Students will discover and understand the moral valuesor concepts of the heros story as a basis for taking certain moral attitudes and actionsthrough the process of internalization, i.e., the developmental changing of behavior whichis controlled externally by internally controlled behavior. The lecture model, as stillpracticed by some teachers in history teaching practice in Indonesia, tends to beindoctrinated and can undermine character education itself.